Peter and Alice : a new play - Logan, John, 1961- (Oberon modern plays., 2013)
'Of course that's how it begins: a harmless fairy tale to pass the hours'When Alice Liddell Hargreaves met Peter Llewelyn Davies at the opening of a Lewis Carroll exhibition in 1932, the original Alice in Wonderland came face to face with the original Peter Pan. In John Logan's remarkable new play, enchantment and reality collide as this brief encounter lays bare the lives of these two extraordinary characters.